Novel approach and setup for multi phase mixtures separation and analysis at offshore conditions - Firas, A.A.K. (Trans Tech Publications Ltd, 2014)
The precious demand not in the push away and broad off from receive forward developed technology approaches place the hand almost several lacks of warns and in-needed developed technique and techniques for greater than before contract and analysis for several issues, no complimentary and talk to studies within the literature describe the system comes in multi component and dual phase particularly for those that ought to be investigated at offshore conditions, the novel technique and setup has been created for such scope, the recently developed discovered has the flexibility to analyses the sorption isotherms and kinetic for multi component and dual phase mixtures (gas and vapor) at offshore conditions in term of temperature up to 150 oC and pressure up to 150 bar. Additionally to the pretreatment that would be finished to the sorbents used at temperatures up to 400 oC and vacuumed pressure. The primer experiments are done using 13 X zeolites for the sorption of pure CO2 at numerous conditions and binary mixtures (CO2 and CH4) with the existence of water vapor. Â© 2014 Trans Tech Publications, Switzerland.